Thermal and Mineral Waters Origin, Properties and Applications - Balderer, Werner; Porowski, Adam.; Idris, Hussein; LaMoreaux, James W.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
This is a compilation of manuscripts on mineral and thermal waters of different areas of the world. This special volume is devoted to the 41st Meeting of the Commission on Mineral and Thermal Waters of International Association of Hydrogeologists (IAH-CMTW) held in Cairo, Egypt, in October 2009. The presentations collected and presented in this volume show the variety of aspects of mineral and thermal waters occurrence and utilization in different countries of the world with a special focus on Egypt, Iran, Ukraine, Poland, Russia and Australia.
1. Saline groundwater ascension problems in East Cairo -- 2. Sinai Peninsula: AN overview of geology and thermal groundwater potentialies -- 3. Enchanced fluoride in groundwater in Eastern Anatolia: effects, origin and possibilities for remediation -- 4. Origin of thermal waters in Budapest based on chemical and isotope investigations including chlorine-36 -- 5. Resources of curative mud in the Crimea Peninsula -- 6. Chemical and isotopic characteristics of thermal waters in the Carpathian Region, South Poland: implication to the origin and resources -- 7. Helwan springs: An overview -- 8. Occurrence of high bicarbonate groundwater in Victoria, Australia -- 9. Industrially valuable components in oil-field waters of Russia.
Keywords: Earth sciences; Renewable energy resources; Hydrogeology; Regional planning; Urban planning; Geophysics; Engineering geology; Engineering -- Geology; Foundations; Hydraulics; Renewable energy sources; Alternate energy sources; Green energy industries; Earth Sciences; Hydrogeology; Renewable and Green Energy; Geoengineering, Foundations, Hydraulics; Landscape/Regional and Urban Planning; Geophysics and Environmental Physics; Electronic books